Assessment of the oral findings, salivary oxidative status and IgA level among group of workers exposed to petroleum pollutants in Al-Daura oil refinery - Hamza, Ameer S; Ahmed , Jamal N (Journal of Baghdad College of Dentistry, 2015)
Background: Oil refinery workers are continuously exposed to numerous hazardous materials. Petroleum contains the heavy metals as a natural constituent or as additives. These metals induce the production of ROS which associated with an oxidative damage to DNA, proteins, and lipids. This study was conducted to assess the salivary levels of heavy metals, salivary oxidative status, oral immunological activity (salivary sIgA) and assessment of the oral findings among the workers of Al-Daura oil refinery in Baghdad city.Subjects, Materials and Methods: This study was done in Al-Daura oil refinery; samples consist of 60 workers involved in refinery processes (study group) and 20 non-workers (control group). Oral examination and saliva collection was done to assess the oral findings and measurement the level of heavy metals (lead and cadmium), oxidative status (MDA and SOD) and secretary IgA.Results: salivary lead and cadmium was higher in study group (6.34 µg/dl and 0.56 µg/l) than that of control group (3.3 µg/dl and 0.34 µg/l) with highly significant difference (p